Metaphysical Aspects of Rose Ausländer’s Poetry - Piasta, Ewa Anna (Respectus Philologicus, 2012)
This article analyzes six poems by Rose Ausländer, a poet of Jewish origin, who lived in the years 1901–1988. She was born at Chernivtsi (then in the Austro-Hungarian Empire), and died in Düsseldorf (Germany). Ausländer wrote in German and in English. The aim of this paper is to discuss the metaphysical aspects of Ausländer’s poems and to demonstrate that these aspects are manifested on the semantic, lexical and axiological levels. My interest is in the spiritual experience evoked by her poetry, resulting from a transcendence-and Absolute-oriented existence, experienced in terms of mystery. Another objective is to determine whether the said metaphysical experience receives religious specification. The ergocentric method, as proposed by Zofia Zarębianka in her research into the sacred in literature, is based on the assumption that this phenomenon is inherent in the text itself and can thus be investigated without referring to external circumstances or searching therein for itsorigins. This allows for a greater concentration onthe very phenomenon of the sacred as present ina literary text.The analysis of the poems shows that references to God the Creator tend to be frequent, and that human participation in the act of creation is repeatedly stressed. The speaker assumes a posture of dependence on, respect for and admiration of the Absolute. Significant to the spiritual dimension of this poetry is seeing material reality and the affairs “of this world” in eschatological terms. Ausländer’s poetry reveals a system of Bible-based beliefs, such as those concerning the love for one’s neighbour. An adequate reading of the meanings evoked in Ausländer’s lyrical texts becomes possible when the Bible is seen as the prototype of the lyrical situations presented in her poems. The primacy of spiritual meanings, as well as the search for identity, eternity, fullness and the creative powers of God, become clear indeed. The religious vocabulary of the poems under discussion is rather poor. Instead, it is axiological references and allusions to Biblical fragments, such as psalm verses, that construct the poems’ metaphysical aspects. These are then made more specific with the use of notions typical of the Judeo-Christian tradition.
Keywords: poetry; metaphysics; transcendence; Rose Ausländer